THE MESSAGE OF PEACE FROM THE VILLAGE: DEVELOPMENT OF RELIGIOUS HARMONY FROM NGLINGGI VILLAGE - Tri Susanto; Sumardjo; Sarwititi Sarwoprasodjo; Rilus A. Kinseng (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
Indonesia is a country with diverse religions, making it the world's most multicultural, plural, and heterogeneous country. The actual conditions are still not in line with the ideals, as conflicts between religious communities are common. Tolerance between religious communities is a perennial issue, owing to the diversity of religions among Indonesians, which leads to religious conflicts. Therefore, in managing the plurality of society, tolerance, equality, and cooperation are needed in social life, resulting in harmony. This study aims to determine the process of developing messages of tolerance and harmony, as well as the promotion process as a role model for other villages. This qualitative research with a case study approach taked the informants from employees of the Nglinggi village office, Klaten Regency, Indonesia. Data was collected using interviews, observations, and documentation to promote tolerance messages that had been built in other villages. The study's results demonstrate that the development of messages of harmony disseminated through the media related to religious community tolerance has a positive impact on other villages as literacy and promotion to build tolerance between religious communities can be applied to other villages.